Enhancing Dissolution and Oral Bioavailability of Ursodeoxycholic Acid with a Spray-Dried pH-Modified Extended Release Formulation - Jaehyeok Lee; Chul Haeng Lee; Jong-Geon Lee; So Yeon Jeon; Min-Koo Choi; Im-Sook Song (MDPI AG, 2022)
Ursodeoxycholate (UDCA) has low oral bioavailability and pH-dependent solubility and permeability. Thus, we developed a pH-modified extended-release formulation of UDCA using Na2CO3 as the alkalizing agent and hydroxypropyl methylcellulose (HPMC) as the release-modifying agent. The optimized pH-modified controlled-release UDCA formulation, with the UDCA:HPMC:Na2CO3 ratio of 200:600:150 (w/w/w), was prepared using a spray-drying method. Then, the formulation's solubility, dissolution, and pharmacokinetic properties were characterized. In a pH-modified extended-release formulation of UDCA, the solubility of UDCA was increased to 8 mg/mL with a sustained dissolution for 12 h. Additionally, the spray-dried formulation exhibited amorphous states without molecular interaction among UDCA, Na2CO3, and HPMC. Moreover, the plasma UDCA concentration of the formulation maintained a higher UDCA concentration for up to 48 h than that of UDCA itself or the non-extended-release UDCA formulation. Consequently, the formulation significantly increased the AUC compared to UDCA or the non-extended-release UDCA formulation in rats. In conclusion, we have improved UDCA's solubility and dissolution profile by preparing a pH-modified extended-release formulation with the UDCA:HPMC:Na2CO3 ratio of 200:600:150 (w/w/w), which effectively increased the oral bioavailability of UDCA by 251% in rats.